Evaluation of the effect of managing oxycodone/acetaminophen as a psychotropic medicine: An interrupted time-series study - Xiang, Cheng; Li, Sha; Zhang, Jinwei; Zhang, Jieqiong; Hu, Shuchen; Pan, Mengyuan; Yang, Caijun; Zhang, Kanghuai (Frontiers in Pharmacology, 2023)
Background Oxycodone/acetaminophen has been reported for misuse frequently in China. To cope with that, Chinese national authorities jointly issued a policy, requiring that oxycodone/acetaminophen should be managed as a psychotropic medicine starting September 1, 2019. This paper aimed to evaluate the effect of this policy in medical institutions. Methods We used interrupted time-series analysis to examine the immediate level and slope changes in the mean number of tablets prescribed, proportion of oxycodone/acetaminophen prescription exceeding 30 pills, days supplied per prescription and the proportion of days supplied exceeding 10 days with prescription data from 5 tertiary hospitals in Xi’an city between January 1, 2018 and June 30, 2021 (42 months). We divided the prescriptions into two groups, one for long-term drug users, and the other for short-term drug users. Results In total, 12,491 prescriptions were included, with 8941 and 3550 prescriptions for the short-term and long-term drug users, respectively. Significant differences in the proportion of prescriptions issued by various departments, were observed between pre- and post- the policy for both short-term and long-term drug users(P<0.001). For short-term drug users, the policy implementation was associated with an immediate level decrease in proportion of prescriptions exceeding 30 tablets (-4.09%, P<0.001). For long-term drug users, after the policy, the mean number of tablets prescribed and the mean proportion of prescriptions exceeding 30 tablets experienced a level decrease of 22.96 tablets (P＜0.001) and a level decrease of 41.13% (P＜0.001), respectively; the mean number of days supplied showed a significant level decrease (6.88 days per prescription) and slope increase (0.19 days per month), and the mean proportion of days supplied exceeding 10 days showed a significant level decrease (-10.51% per prescription) and a slope increase (0.27% per month). Conclusion Implementation of stricter management for oxycodone/acetaminophen achieved its goal of reducing the risk of misuse in short-term drug users. For long-term drug users, policy needed to be strengthened as the prescription exceeding 10 days was still at a high level after the intervention. Policies targeting patients with different drug demands are needed. Many other strategies can be implemented, including establishing specific guidelines and conducting training programs.